Drug resistance in liver flukes. (April 2020) - Fairweather, I.; Brennan, G.P.; Hanna, R.E.B.; Robinson, M.W.; Skuce, P.J.
Abstract: Liver flukes include Fasciola hepatica, Fasciola gigantica, Clonorchis sinensis, Opisthorchis spp., Fascioloides magna, Gigantocotyle explanatum and Dicrocoelium spp. The two main species, F. hepatica and F. gigantica, are major parasites of livestock and infections result in huge economic losses. As with C. sinensis, Opisthorchis spp. and Dicrocoelium spp., they affect millions of people worldwide, causing severe health problems. Collectively, the group is referred to as the Food-Borne Trematodes and their true significance is now being more widely recognised. However, reports of resistance to triclabendazole (TCBZ), the most widely used anti- Fasciola drug, and to other current drugs are increasing. This is a worrying scenario. In this review, progress in understanding the mechanism(s) of resistance to TCBZ is discussed, focusing on tubulin mutations, altered drug uptake and changes in drug metabolism. There is much interest in the development of new drugs and drug combinations, the re-purposing of non-flukicidal drugs, and the development of new drug formulations and delivery systems; all this work will be reviewed. Sound farm management practices also need to be put in place, with effective treatment programmes, so that drugs can be used wisely and their efficacy conserved as much as is possible. This depends on reliable advice being given by veterinarians and other advisors. Accurate diagnosis and identification of drug-resistant fluke populations is central to effective control: to determine the actual extent of the problem and to determine how well or otherwise a treatment has worked; for research on establishing the mechanism of resistance (and identifying molecular markers of resistance); for informing treatment options; and for testing the efficacy of new drug candidates. Several diagnostic methods are available, but there are no recommended guidelines or standardised protocols in place and this is an issue that needs to be addressed. Graphical abstract: Image 1 Highlights: Liver flukes are major parasites of humans and livestock and cause severe disease. Resistance to triclabendazole and other flukicides is becoming a serious problem. The mechanism of resistance to triclabendazole is not clear, but may have a polygenic basis. Possible treatment and management strategies to deal with resistance are discussed. Several diagnostic tests are available, but no recommended guidelines are in place.